2017
DOI: 10.3389/fcimb.2017.00108
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the A. baumannii A1S_0114 Gene to the Interaction with Eukaryotic Cells and Virulence

Abstract: Genetic and functional studies showed that some components of the Acinetobacter baumannii ATCC 17978 A1S_0112-A1S_0119 gene cluster are critical for biofilm biogenesis and surface motility. Recently, our group has shown that the A1S_0114 gene was involved in biofilm formation, a process related with pathogenesis. Confirming our previous results, microscopy images revealed that the ATCC 17978 Δ0114 derivative lacking this gene was unable to form a mature biofilm structure. Therefore, other bacterial phenotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 51 publications
(101 reference statements)
4
32
1
Order By: Relevance
“…The reduction might be due to the decreased translocation of molecules related to this type of motility, such as surfactants or quorum-sensing signals [5,8,10]. Accordingly, one of the most strongly down-regulated genes of an A. baumannii cheA/Y-like mutant belongs to the operon A1S_0112-0119, involved in the production of acinetin 505 and its extrusion via an RND efflux pump [12,27]. Acinetin 505 is a lipopeptide that may act as a surfactant in the promotion of surface-associated motility [27].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction might be due to the decreased translocation of molecules related to this type of motility, such as surfactants or quorum-sensing signals [5,8,10]. Accordingly, one of the most strongly down-regulated genes of an A. baumannii cheA/Y-like mutant belongs to the operon A1S_0112-0119, involved in the production of acinetin 505 and its extrusion via an RND efflux pump [12,27]. Acinetin 505 is a lipopeptide that may act as a surfactant in the promotion of surface-associated motility [27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inactivation of the gene A1S_0114, involved in the synthesis of a lipopeptide, reduces the motility and virulence of A. baumannii. A1S_0114 is located on the same operon as A1S_0116, which encodes an RND transporter possibly involved in the secretion of this lipopeptide (23).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of AgNPs with different cell models and their cellular effect have been reviewed recently (30) and showed the involvement of ROS during interaction of AgNPs with different cell lines. Recently, it is also reported that acinetin-505, a small lipopeptide-like compound, have role in the interaction of A. baumannii with pulmonary cells model (31). Most of the studied done so far have highlighted the use of AgNPs against A. baumannii in suspension form but less have been studied about the inhibitory role of AgNPs in the infection of A. baumannii to the human cell model.…”
Section: Discussionmentioning
confidence: 99%